DETERMINATION OF LOCAL DIAGNOSTIC REFERENCE LEVEL (LDL) PEDIATRIC PATIENTS ON CT HEAD EXAMINATION BASED ON SIZE-SPECIFIC DOSE ESTIMATES (SSDE) VALUES - Latifah, Risalatul; Jannah, Naily Z.; Nurdin, Dezy Z.I; P, Budi (Faculty of Vocational Studies, Universitas Airlangga, 2019)
Background: CT Scan provides the biggest contribution in receiving radiation doses in patients. Especially in pediatric patients or children. Local DRL (Diagnostic Reference Level) is an effort to optimize radiation for patients in every health facility. During this time the LDRL value is determined from the CTDIvol displayed from the CT Scan workstation. However, CTDI has a weakness which is irrelevant for wide-beam CT and is only a tool output dose, not paying attention to patient size. SSDE is a dose correction based on the patient's geometry. Purpose: This study aims to determine the estimation of pediatric patient dose profiles on head CT scan based on SSDE values to determine LDRL. Method: The study was conducted by collecting data on pediatric patient doses with an age range of 0-1 years, 2-5 years and 6-10 years who underwent a head CT scan within the period from July to December 2017. The samples were measured lateral and anterior-posterior diameter for determine the correction factor. The results of the CTDIvol record and conversion factor will determine the SSDE value. The third quartile data from SSDE is specified as LDRL. The SSDE value in the three groups shows the same trend which is smaller than the CTDIvol value. The correction of the factor gives estimates of doses received by patients reduced by 2.6%, 8.5% and 20% respectively for ages 0-1 years, 2-5 years and 6-10. Acceptance of patient doses is influenced by tube tension, filament current, rotation time, scan length, number of phases and pitch. Conclusion: From the results of the SSDE value, DRL values can be determined for the age group 0-1 years, 2-5 years and 6-10 years respectively 23,1±1,5 mGy, 24,3± 1,8 mGy and 27, 5± 10,5mGy.